Design for the mind : seven psychological principles of persuasive design - Yocco, Victor S., 1978- (Manning Publcations, 2016)
Design for the Mind: Seven Psychological Principles of Persuasive Design teaches web designers and developers how to create sites and applications that appeal to our innate natural responses as humans. Author Victor Yocco, a researcher on psychology and communication, introduces the most immediately relevant and applicable psychological concepts, breaks down each theory into easily-digested principles, then shows how they can be used to inform better design. About the Technology Designers and design team members need to think about more than just aesthetics. How do you handle short attention spans. How does your design encourage users to engage, browse, or buy? Fortunately, there are psychological principles that you can use in your design to anticipate and benefit from how humans think, behave, and react. About the Book Design for the Mind: Seven Psychological Principles of Persuasive Design teaches you to recognize how websites and applications can benefit from an awareness of our innate, natural responses as humans, and to apply the same principles to your own designs. This approachable book introduces the psychological principles, deconstructs each into easily digestible concepts, and then shows how you can apply them. The idea is to deepen your understanding of why people react in the ways they do. After reading the book, you'll be ready to make your work more psychologically friendly, engaging, and persuasive. What's Inside Making design persuasive Encouraging visitors to take action Creating enduring messages Meeting the needs of both engaged and disengaged visitors Becoming a strategic influencer Applying theory, with case studies and real-world examples About the Reader This book is for web and UX designers and developers as well as anyone involved in customer-facing digital products. About the Author Victor Yocco, PhD, is a research director at a Philadelphia-based digital design firm. He received his PhD from The Ohio State University, where his research focused on psychology and communication in informal learning settings. Victor regularly writes and speaks on topics related to the application of psychology to design and addressing the culture of alcohol use in design and technology. He can be found at www.victoryocco.com or @victoryocco on Twitter.